Scorpion toxin MeuNaTxα‐1 sensitizes primary nociceptors by selective modulation of voltage‐gated sodium channels. (5th November 2020) - van Cann, Marianne; Kuzmenkov, Alexey; Isensee, Jörg; Andreev‐Andrievskiy, Alexander; Peigneur, Steve; Khusainov, Georgii; Berkut, Antonina; Tytgat, Jan; Vassilevski, Alexander; Hucho, Tim
Abstract : Venoms are a rich source of highly specific toxins, which allow the identification of novel therapeutic targets. We have now applied high content screening (HCS) microscopy to identify toxins that modulate pain sensitization signaling in primary sensory neurons of rat and elucidated the underlying mechanism. A set of venoms and fractions thereof were analyzed for their ability to activate type II protein kinase A (PKA‐II) and extracellular signal‐regulated kinases (ERK1/2). We identified MeuNaTxα‐1, a sodium channel‐selective scorpion α‐toxin from Mesobuthus eupeus, which affected both PKA‐II and ERK1/2. Recombinant MeuNaTxα‐1 showed identical activity to the native toxin on mammalian voltage‐gated sodium channels expressed in Xenopus laevis oocytes and induced thermal hyperalgesia in adult mice. The effect of MeuNaTxα‐1 on sensory neurons was dose‐dependent and tetrodotoxin‐sensitive. Application of inhibitors and toxin mutants with altered sodium channel selectivity demonstrated that signaling activation in sensory neurons depends on NaV 1.2 isoform. Accordingly, the toxin was more potent in neurons from newborn rats, where NaV 1.2 is expressed at a higher level. Our results demonstrate that HCS microscopy‐based monitoring of intracellular signaling is a novel and powerful tool to identify and characterize venoms and their toxins affecting sensory neurons. Abstract : Nociceptors are specialized sensory neurons that initiate the perception of pain. We applied high content screening microscopy to screen animal venoms for toxins, which activate pain enhancing signal transduction in sensory neurons. We identified the scorpion α‐toxin MeuNaTxα‐1 from Mesobuthus eupeus, which selectively affected tetrodotoxin‐sensitive voltage‐gated sodium channels, in particular NaV 1.2, and thereby depolarized the nociceptors, leading to calcium influx, subsequent PKA‐II activation, and thermal hyperalgesia.